Oral Contraceptives and Ovarian Steroid Hormones: The Effects on the Brain and Behaviour in Young Adult Women - Sharma, Rupali (Université d'Ottawa / University of Ottawa, 2020)
Puberty is a critical period of development characterized by rapid physiological changes and significant brain reorganizing and remodeling in women. These rapid changes render the developing brain particularly vulnerable to stress and exogenous factors. According to recent trends, women are increasingly likely to begin using exogenous/synthetic hormones (i.e., oral contraceptives; OCs) as early as during puberty. While millions of women worldwide use OCs, the extent of OC-related structural, functional, and behavioral changes and the role of ovarian steroid hormones remain elusive. Thus, we hypothesized that hormonal modulation through OC use during puberty would result in unique neural and behavioural outcomes compared to OC use later in life. The current thesis examined the effects of OC use, especially during puberty, on cortisol reactivity, brain structure, and brain function during a working memory cognitive task (Article 1). Next, we examined whether the task-related functional differences between OC users and non-OC users could be informed by resting state functional connectivity in the default mode, salience, central executive, and, reward networks (Article 2). Lastly, we examined the roles of progesterone and estradiol on emotion processing during the cognitive task in all women (Article 3). The current dissertation has addressed OC-related differences to the brain and behaviour and the influence of ovarian steroid hormones in these differences. These studies have demonstrated that OC use is related to specific structural and functional differences, with some findings being dependent on the age of OC onset and duration of OC use. The findings offer critical insight into women’s brain health and bring awareness to the potential behavioural and neural consequences of OC use and role of ovarian steroid hormones.
Keywords: Oral Contraceptives; Stress Reactivity; Brain Imaging; Puberty/Adolescence